Management: Izbrana poglavja (University of Maribor Press, 2022)
Management: Selected chapters. Scientific monograph Management - selected chapters are focused on certain contents of management in various fields, which, through scientific research and their connection with applicability, focus on development trends. Given the complexity or. diversification of management into virtually all spheres of our lives, it is impossible to cover consistently everything in one scientific monograph. Therefore, we decided to choose such chapters, which, however, cover sufficient multi-disciplinarity and thus allow researchers and researchers of management to see the processes and directions of the path in the near future of development.